Transplantation of human Wharton's jelly-derived mesenchymal stem cells highly expressing TGFβ receptors in a rabbit model of disc degeneration. Issue 1 (December 2015) - Ahn, Jongchan; Park, Eun-mi; Kim, Byeong; Kim, Jin-Soo; Choi, Bogyu; Lee, Soo-Hong; Han, Inbo
Abstract Introduction Mesenchymal stem cells (MSCs) are widely considered to hold promise for the treatment of intervertebral disc (IVD) degeneration. However, variation in the therapeutic efficacy of MSCs is a major problem and the derivation of MSCs for use in IVD regeneration has not been optimized. Additionally, no data are available on the efficacy of Wharton's Jelly-derived MSC (WJ-MSC) transplantation in an animal model of IVD degeneration. Methods This study evaluated the effectiveness of a cross-linked hyaluronic acid (XHA) scaffold loaded with human WJ-MSCs, according to their expression levels of transforming growth factor-β receptor I/activin-like kinase receptor 5 (TβRI/ALK5) and TβRII, for IVD regeneration in a rabbit model. We compared the degree of IVD regeneration between rabbits transplanted with a XHA scaffold loaded with WJ-MSCs highly and lowly expressing TβRI/ALK5 and TβRII (MSC-highTR and MSC-lowTR, respectively) using magnetic resonance imaging (MRI) and histological analysis. Results At 12 weeks after transplantation, T2-weighted MRI analysis showed significant restoration of the disc water content in rabbits treated with a MSC-highTR-loaded XHA scaffold in comparison to rabbits treated with the scaffold alone or a MSC-lowTR-loaded XHA scaffold. In addition, morphological and histological analyses revealed that IVD regeneration was highest in rabbits transplanted with a MSC-highTR-loaded XHA scaffold. Conclusion Taken together, our results suggest that a MSC-highTR-loaded XHA scaffold supports IVD regeneration more effectively than a MSC-lowTR-loaded XHA scaffold. This study supports the potential clinical use of MSC-highTR-loaded XHA scaffolds to halt IVD degeneration or to enhance IVD regeneration.